A Multimodal Analysis of an Indonesian Recipe Book - Sugiharti, Esti; Koesoemah, Nita Henita (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
This article is about a multimodal analysis of an Indonesian cookbook entitled Indonesian Cakes & Desserts by Wongso and Tobing (2002) written in English intended for English speakers. The aim is to show how writing and images relations are used to convey the meanings of the recipes. Cookbooks from non-English culture written in English have rarely become the subject of research using a multimodal approach. Such cookbooks may create a problem to the audiences as they may not be familiar with the food. Therefore, it is important to investigate how writing and images in the Indonesian cookbook are integrated to be understood by the English audience. The intermodal text-image integration from Unsworth and ClÃ©irigh (2009) is used to show how writing and images are integrated in the cookbook to construct meanings. The results are that the intensive identification of images and language is used to introduce some ingredients, and the intermodal circumstantial identifications of locations visualizing Manner: quality and Causal-condition: result are used to explain some steps on how to cook the food in some recipes. These findings may contribute to expand the use of intermodal text-image integration in texts introducing items or processes that are foreign to the reader.